Examining the Detrimental Impact of “Kiss Up, Kick Down” Office Culture in Vietnam: A Qualitative Exploration using Grounded Theory - Pham, Thuy Trut; Thao, Le Thanh; Tran, Thuy Thi (Jurnal Komunikasi Pendidikan, 2023)
This study aimed to explore the “Kiss up, kick down” culture in Vietnamese educational institutions and understand its implications on teachers at different stages of their career: novice, mid-career, and near-end. Using a qualitative approach, 15 participants were interviewed. The thematic analysis of interview data resulted in the identification of fifteen themes. They highlighted a pervasive culture driven by power dynamics and hierarchy, impacting interpersonal relationships, job satisfaction, professional growth, and mental well-being. Additionally, the culture was found to align with societal norms and was seen as a reflection of the collective culture and historical influences in Vietnam. The study underscores the need for systemic change and offers insights that could inform policy and practice aimed at creating healthier and more inclusive academic environments.